PERANCANGAN INOVASI PRODUK MODEL 11LTC DENGAN METODE QUALITY FUNCTION DEPLOYMENT DAN DESIGN FOR MANUFACTURING ASSEMBLY DI PT. FJT BATAM - Arifin, Zaenal (SIGMA TEKNIKA, 2024)
The activity of designing and developing products, whether in the form of goods or services, cannot be separated from the marketing concept which aims to fulfill customer needs. Customer satisfaction can be met by identifying consumer behavior towards a product. Consumer behavior towards a product can be detected by appealing to market needs (Market Full), suppressing market penetration with new technology (technology Push), and modifying potential products to be offered to the market (Platform Product) The aim of this research is to find out what consumer needs are for a product by using the Quality Function Deployment Method and Design For Manufacturing Assembly, to increase consumer satisfaction and reduce part costs and process costs in the company. Based on the results of this product development, the company makes products according to consumer desires and can save costs on product material parts and costs on product processes